Sorbus oravica (Rosaceae), a new remarkable endemic of Sorbus subgen. Soraria from Slovakia - Velebil, Jiří; Lepší, Martin; Lepší, Petr; Nosková, Jana; Bernátová, Dana (Phytotaxa, 2025)
A newly discovered species, Sorbus oravica, from northern and east-central Slovakia is described and illustrated, with a detailed account of its distribution. It is classified within the Sorbus subgen. Soraria and identified as an apomictic tetraploid species. The separation of S. oravica from related taxa was supported by molecular analyses (nuclear microsatellite markers) and extensive morphological comparisons. In addition, a determination key including all S. subgen. Soraria taxa occurring in Slovakia is provided.